Implementasi Pembelajaran Norma Agama dan Moral di Raudlatul Athfal Al Munawwarah Slarang - Sakiyem Sakiyem (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2022)
This study aims to determine the implementation of learning religious and moral norms at RA Al Munawwarah Slarang. This research is a qualitative descriptive study. The subjects of this study were homeroom teachers, principal and students of RA Al Munawwarah Slarang. Data collection techniques in the form of observation, interviews and documentation. Data analysis techniques use the Miles & Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of learning religious and moral norms at RA Al Munawwarah Slarang are carried out by providing materials that are useful as provisions for children in living life such as material on faith, worship and morals. Faith material in the form of an introduction to the pillars of faith, worship material in the form of the pillars of Islam. Whereas moral material in the form of planting commendable behavior in everyday life. Methods for learning religious and moral norms at RA Al Munawwarah Slarang include the singing method, the assignment method, the rote method, the question and answer method, the exemplary method, the iqra method, the lecture method, the storytelling method, the rhyme method and the field trip method. These methods are used interchangeably and varied with the aim of attracting the attention of students so they don't get bored in following the learning process.